Representación de las actividades cotidianas de los campesinos de las zonas periféricas en la ciudad de Loja a través del realismo en la pintura - Sanches Bao, Pablo Andrés (2019)
The present investigation considers the analysis of the artistic current of realism within the painting for the generation of a pictorial proposal based on the daily life of the peasants who are in the peripheral areas of the city of Loja. In order to retake the painting that represents the peasant, and thus sensitize the viewer, taking into account that realism defends contemporaneity against historicity: there is a need for the being of his time. Therefore, there is a need to represent the peasant in order to exalt his sacrificial work and his way of life, which transmits his soul so that he can transmit it to the canvas